2004
DOI: 10.1074/jbc.m410814200
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB1 Is Essential in T-cell-T-cell Co-operation during T-cell Activation

Abstract: Eph kinases are the largest family of receptor tyrosine kinases, and their ligands are ephrins (EFNs), which are also cell surface molecules. We have very limited knowledge about the expression and function of these kinases and their ligands in the immune system. In this study we investigated the effect of EFNB1 on mouse T-cells. EFNB1 and the Eph kinases it interacts with (collectively called EFNB1 receptors (EFNB1R)) were expressed on T-cells, B cells, and monocytes/macrophages. Some T-cells were double posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 50 publications
1
79
1
Order By: Relevance
“…Its reverse signaling depends on adaptor proteins associating with the tail. EFNB2 intracellular tails are characterized by two major features: the C-terminal PDZ domain-binding motif and five conserved tyrosine residues, which could be associated with PDZ domaincontaining proteins (eg, PDZ-RGS3, GRIP1/2, TIAM1 and DISHEV-ELED) 3,17,21,37,38 and SH2 domain-containing proteins (eg GRB4, STAT3 and CRK, 39 respectively). These two features are located in the last 31 aa, which are highly conserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its reverse signaling depends on adaptor proteins associating with the tail. EFNB2 intracellular tails are characterized by two major features: the C-terminal PDZ domain-binding motif and five conserved tyrosine residues, which could be associated with PDZ domaincontaining proteins (eg, PDZ-RGS3, GRIP1/2, TIAM1 and DISHEV-ELED) 3,17,21,37,38 and SH2 domain-containing proteins (eg GRB4, STAT3 and CRK, 39 respectively). These two features are located in the last 31 aa, which are highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[12][13][14][15][16][17][18][19][20][21][22] They are also vital in many biological processes; 5,6,23,24 however, until our recent publications, there were no studies investigating the roles of these molecules in blood pressure (BP) regulation.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that Efnb1, Efnb2, and Efnb3 initiate signaling through their Eph receptors and can costimulate peripheral T cells in terms of enhancing cytokine production and proliferation in vitro (25)(26)(27). We further demonstrated that one of these Efnb receptors, Ephb6, although lacking kinase activity, can transmit signals into T cells (28) and that its null mutation leads to compromised T cells responses in vitro and in vivo (29).…”
Section: Ephsmentioning
confidence: 99%
“…Flow Cytometry-Single cell suspensions from the thymus, spleen, or lymph nodes were prepared and stained for flow cytometry as described in our previous publications (25)(26)(27)(28)(29) tetrameric complexes were synthesized in-house and used at 1:100 dilution as described previously (30). These MHC tetramers were used to detect LCMV-specific CD8 ϩ T cells.…”
Section: Generation Of T Cell-specific Efnb1 and Efnb2mentioning
confidence: 99%
“…The urothelium accomplishes this by forming a top layer of highly differentiated umbrella cells that elaborate a specialized apical asymmetric unit membrane. This unique membrane structure is composed mainly of four integral membrane proteins, the uroplakins Ia, Ib, II, and III (1)(2)(3)(4)(5)(6). These proteins begin to assemble in the endoplasmic reticulum where they form specific dimers (7)(8)(9), and they assemble further in a post-Golgi compartment represented by discoidal vesicles, where they form increasingly larger crystalline arrays composed of 16-nm hexagonal particles (1,(10)(11)(12)(13).…”
mentioning
confidence: 99%